Non-destructive evaluation and Structural Health Monitoring of impact induced damage in composite structures using ultrasonic approaches and shearography - Memmolo, Vittorio; Maio, Leandro; Monaco, Ernesto; Ricci, Fabrizio; Vespini, Veronica; Graziano, Fabiana; Grilli, Simonetta; Coppola, Sara; Ferraro, Pietro (E-journal of Nondestructive Testing, 2024)
Composite structures are massively used thanks to the high strength-to-weight ratio, making them ideal for lightweight and durable structures in aviation. However, Impact may arise at any time during lifetime on composite aerostructures and ensuring their structural integrity via fast inspection is essential to meet airworthiness criteria. Multimodal NDT (Non-Destructive Testing) inspection and characterization of composite structures is a critical process to verify the quality of the composite material and identify any defects. In this context, the paper shows a comparison of several techniques as nondestructive methods: shearography, laser ultrasonics and phased array ultrasonics. In particular, using shearography and laser ultrasonics as non-contact approaches can increase the inspection speed and reliability compared to the state of the art phased array ultrasonics, which is the standard approach used in the aerospace field. For this reason, a sample of interest to the aerospace industry is subject to different low velocity impacts which are characterized by different energies leading to barely visible damage. The results show the capabilities of both approaches in identifying small emerging defects along with the advantage and drawbacks of both methodologies through a critical review of performance thereof evaluating the parameters of their use. In addition, the same approaches are adopted on a stiffener composite plates and compared with continuous health monitoring approaches. In this regard, NDT approaches are demonstrated useful to enhance the SHM warnings.